Review: Modeling Damping in Mechanical Engineering Structures - Michel Lalanne (Shock and Vibration)
This paper is concerned with the introduction of damping effects in the analysis of mechanical engineering structures. Damping can be considered as being generated by concentrated elements, by distributed elements, or by several effects existing simultaneously. Modeling damping for different engineering situations is described and some applications are presented briefly.